ENRICHING STUDENTS’ VOCABULARY MASTERY BY USING ANIMATION VIDEOS AS A LEARNING MEDIA AT SEVENTH GRADE OF SMP IT HAYYUN SASMITA - Muhammad Khoerul Hadist; Siti Hodijah (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
This was qualitative research. The objective of this research is to investigated the using animation videos toward students’ vocabulary mastery. There were 36 participants involved at seventh grade of SMP Hayyun Sasmita (Junior High School) Bogor. Observation and documentation employed as data collecting technique. The observation conducted to know student learning attitude while using this animation video strategy and the documentation date attached to proving student vocabulary performance during using animation video strategy. Based on thus technique collecting data, the result revealed that, students’ vocabulary was increasing by using video animation strategy. The student communicative, interested, and mastering vocabulary as the variable result during research conducted.